Textronics—A Review of Textile‐Based Wearable Electronics. Issue 12 (21st August 2021) - Choudhry, Nauman A.; Arnold, Lyndon; Rasheed, Abher; Khan, Imtiaz A.; Wang, Lijing
Abstract : Textronics contribute a significant part of Internet‐of‐Things (IoT), which empowers added functionalities by connecting smart clothing in a secure way for diverse applications. For the development of flexible and stretchable textile‐based electronics, a conductive material (yarn, fabric, etc.) must be used, and fabrication techniques play a vital role that significantly influences electronic textiles' properties. Textile‐based sensors, electrodes, and other devices seem to be the favorite choice for continuous wearable monitoring due to their low cost, flexibility, and ease of embedding. Integrating smart capabilities into textiles provides substantial benefits in the fields of healthcare, sports, automobile, and military. These developments have a profound influence on the Fourth Industrial Revolution (4IR). This Review presents an in‐depth study of the current state of the art in the area of textile‐based electronics. The design, development, and evaluation techniques are discussed. Certain limitations and research gaps are also addressed regarding this emerging field. Critically, this Review is more application focused and indicates how the recent developments in electronic textiles will soon impact our lives. As these areas have typically been neglected in previous reviews, additional knowledge to the existing literature is provided by bridging the gap between the academic research and commercialization of wearable Textronics. Abstract : The Review summarizes the textile‐based wearable electronics including textile‐based sensors, electrodes, heating textiles, energy‐harvesting textiles, energy storage devices, and textile‐based communication. It is more application‐focused and indicates how the recent developments in electronic textiles will soon impact our lives. Some of the most promising commercial applications of wearable electronics and their evaluation techniques are also discussed.